Estudo das alterações renais e vasculares induzidas pelo veneno de Tityus serrulatus - Alves, Renata de Sousa (2005)
According to the Brazilian Ministry of Health, about 8000 cases of scorpion envenomation are reported yearly in Brazil. Most cases are due to the sting of Tityus serrulatus, known popularly as yellow scorpion. It belongs to the Arachnidea, class, Scorpionidae order, Buthidae family, Tityinae subfamily and Tityus genus. It is present in the Brazilian States of Minas Gerais, Espírito Santo, Bahia, Rio de Janeiro, São Paulo, Paraná, Goiás, Mato Grosso do Sul and Ceara and it is the most dangerous scorpion in Brazil, causing severe envenoming and even death. The effects of T. serrulatus venom (TsV) on the renal physiology in humans consist of increased renal parameters such as urea and creatinine. So far, effects had not been tested in the perfused rat kidney. Isolated kidneys from Wistar rats, weighing 250 to 300g, were perfused with Krebs-Henseleit solution containing 6g% of previously dialysed bovine albumin. The effects of T. serrulatus venom in the 1, 3 and 10 μg/mL concentrations, were studied on the perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF), glomerular filtration rate (GFR), sodium tubular transport (%TNa+), potassium tubular transport (%TK+) and chloride tubular transport (%TCl-). Tityus serrulatus venom was added to the system after 30 minutes of internal control; it increased PP (PP30’ = 112.4 ± 2.0 vs PP60’ = 145.8 ± 17.4mmHg*,*p<0.05) and RVR (RVR30’ = 5.88 ± 0.33 vs RVR60’ = 7.52 ± 0.86mmHg/mL.g-1.min-1*,*p<0.05), decreased GFR (GFR30’ = 0.671 ± 0.076 vs GFR120’ = 0.467 ± 0.062mL.g-1.min-1*,*p<0.05) and UF (UF30’ = 0.147 ± 0.011 vs UF90’ = 0.119 ± 0.013mL.g-1.min-1*,*p<0.05). The mesenteric bed was perfused with Krebs solution kept warm at 37ºC by a constant flow (4mL/min), while the variable perfusion pressure was measured by means of a pressure transducer. The vascular effects of T. serrulatus venom were examined and compared to the infusion of the perfuse solution. The infusion of T. serrulatus venom (10μg/mL/min) increased the basal perfusion pressure of isolated arteriolar mesenteric bed (basal pressure = 74.17 ± 3.42 vs TsV = 151.8 ± 17.82 mmHg*,*p<0.05). The histopathological evaluation revealed deposits of protein in the renal tubules and urinary spaces of kidneys perfused with TsV. This may reveal that there has been a perfusate extravasation to the parenchyma probably due to increase of hydrostatic pressure induced by TsV. T. serrulatus venom affects renal hemodynamics increasing resistance and perfusion pressure, determining extravasation of perfusate and decreasing the glomerular filtration rate and renal flow.